TRAINING RESEARCH AND ENGINEERING ELITE FOR RUSSIAN DEFENSE INDUSTRY - Igor B. Fedorov; Valentin E. Medvedev (Высшее образование в России)
The paper deals with the problem of qualified personnel shortage in science intensive spheres of economy and analyzes the factors contributing to raising of the quality of young specialist training and further employment in high-tech industry. A framework of actions to solve the personnel problem in defense industry is given.